ANALYZING GENDER DIFFERENCES, AND EDUCATION OF PARENTS TOWARDS STUDENTS’ READING COMPREHENSION ACHIEVEMENT - Ardiansyah, Welly; Ujihanti, Murwani; Aryanti, Nurul (International Online Journal of Education and Teaching, 2020)
The aim of the study was to find out: students’ gender differences, and parental education on students’ reading comprehension achievement. The sample was 100 students and used purposive random sampling. Interview and the forty-item reading comprehension test of multiple choices were administered. The data were analyzed with one-way ANOVA. The first finding showed that females’ reading comprehension achievement was higher than males’. The second finding showed that variable “fathers’ level of education” and “students’ reading comprehension achievement” was .029 categorized “weak”. The third finding showed that the correlation between variable “mothers’ level of education” and variable “students’ reading comprehension achievement” was .530** categorized “strong”. The effect of mother’s education occurred through the provision of literacy resources and reading activities. Mothers spent more time with their children at home, continuously nurturing them with practices such as reading, and holding discussions with them on how they handle their studies. While fathers did not involve themselves and became reluctant to help their children to do their schoolwork at home. Some stated that they were not lecturers and busy working to earn their families living. The study recommended that both parents should collaborate to create a reading atmosphere in their family.